1986
DOI: 10.1071/ch9860541
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal-Structure of Silver(I) (2-Carbamoylphenoxy)Acetate

Abstract: The crystal structure of anhydrous silver(I)(2-carbamoylphenoxy)acetate has been determined by X-ray diffraction and refined to a residual of 0.041 for 1532 observed reflections. The complex forms crystal: with space group C2/c and Z4 in a unit cell of dimensions a 20.789(6), b 5.202(1) c 17.318(6)Ǻ, β 105.89(2)°. The structure is based on a centrosymmetric bis-carboxylate bridged dimer [Ag-O 2.228(3), 2.266(3)Ǻ, O-Ag-O 155.8(1)°; Ag…Ag 3.001(1)Ǻ] which is extended into an infinite zigzag polymer through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The method used for preparing [Ag 2 (NH 3 ) 2 (salH) 2 ] was quite similar to that employed for the preparation of the known non-amine analogue [Ag 2 (salH) 2 ] [4][5][6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used for preparing [Ag 2 (NH 3 ) 2 (salH) 2 ] was quite similar to that employed for the preparation of the known non-amine analogue [Ag 2 (salH) 2 ] [4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…[Ag 2 (salH) 2 ] was prepared in accordance with the literature procedure [4][5][6]. Infrared spectra of solids (in a KBr matrix) were recorded in the region 4000-400 cm À1 on a Nicolet FT-IR Impact 400D infrared spectrometer and 1 H NMR spectra were run on a Bruker Avance 300 MHz instrument.…”
Section: Methodsmentioning
confidence: 99%
“…1). This structure is similar to that found in silver(I) (2-carbamoyphenoxy) acetate (Mak et al, 1986) and results from the presence of additional Ag-Ο bonds from each of the terminal positions of the dimer to the hydroxyl oxygens of adjacent dimers [0(2)"; -1/2 +λ:, 1/2-y, 1/2+z: 2.607 ( Acknowledgements. The authors thank The University of Queensland, The Chinese University of Hong Kong and the Queensland University of Technology for financial assistance.…”
Section: Discussionmentioning
confidence: 73%
“…X y ζ Ag 437.9(7) 1208.9(3) 264.5(5) 49.9(2) C(l) 2443 (6) 190 (3) -4751 (5) 25(2) C(2) 2925(6) 1245(4) -5473 (5) 29(2) C(3) 3595 (7) 1304(4) -7062(6) 35(2) C(4) 3781 (7) 304 (5) -7943 (5) 35(2) C(5) 3332 (7) -757(4) -7281(5) 36(2) C (6) 2694 (6) -812(4) -5693 (5) 29(2) C (7) 1719 (6) 140 ( (2) systematics to be described (Mak et al, 1986), and while one example is known in which an open-chain polymer is found (Mak et al, 1988 a), the majority are based on variations of the bis-carboxylato (0,0') dimer. Among these, the structure of silver(I) 2,6-dihydroxybenzoate (Smith et al, 1988) was a centrosymmetric, type 1 bis-carboxylato(O.O') dimer, similar to silver(I) salicylate (Smith et al, 1988), silver(I) benzoate and silver(I) 4-hydroxybenzoate (Usubaliev et al, 1981) and silver(I) (2,3,4,5,6-pentafluorophenoxy)acetate (Mak et al, 1988 b).…”
Section: Introductionmentioning
confidence: 99%
“…Dimeric silver(I) carboxylates have been categorised into four distinct types (Mak et al, 1986). The Type 1 complexes, which are essentially * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%